(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Diabetic is known to be the main non-commutable public health concern. In this study, we evaluated the relationship between diet, body weight and accumulation of adipose tissue in healthy, diabetic and prediabetic rats. Physiologically, adipose tissue plays a central role in lipid and glucose metabolisms. Therefore, accumulation of adipose tissue in diabetic and prediabetic may lead to others non-commutable diseases. The rats in control, diabetic and prediabetic groups were fed with normal and high fat diets for 6 consecutive weeks, while the rats in 4 sub-groups of diabetic and prediabetic groups also received metformin, a common drug to control diabetes. The results indicated that in diabetic rats, a small increase of food calories by high fat diet caused a significant gained in body weight and a significant increase in adipose tissue accumulation with or without metformin treatment, however in prediabetic rats, rats with metformin treatment shown to be beneficial in maintaining body weight and adipose accumulation. The data of the study imply that balance diet at high calories should be practiced by patients as high fat diet with similar calories can caused a significant health deterioration to the patients in term of body weight gained and adipose tissue accumulation.